Gender on the market : Moroccan women and the revoicing of tradition - Kapchan, Deborah A. (Deborah Anne) (New cultural studies., 1996)
Selected by Choice magazine as an Outstanding Academic Book for 1996Gender on the Market is a study of Moroccan women's expressive culture and the ways in which it both determines and responds to current transformations in gender roles. Beginning with women's emergence into what has been defined as the most paradigmatic of Moroccan male institutions--the marketplace--the book elucidates how gender and commodity relations are experienced and interpreted in women's aesthetic practices. Deborah Kapchan compellingly demonstrates that Moroccan women challenge some of the most basic cultural assumptions of their society--especially ones concerning power and authority.